Influence of ingesting a carbohydrate-electrolyte solution before and during a 1-hour run in fed endurance-trained runners - Rollo, I.; Williams, C. (Journal of Sports Sciences, 2010)
The aim of this study was to determine whether the ingestion of a carbohydrate-electrolyte solution would improve 1-h running performance in runners who had consumed a meal 3 h before exercise. Ten endurance-trained male runners completed two trials that required them to run as far as possible in 1 h on an automated treadmill that allowed changes in running speed without manual input. Following the consumption of the pre-exercise meal, which provided 2.5 g carbohydrate per kilogram body mass (BM), runners ingested either a 6.4% carbohydrate-electrolyte solution or placebo solution (i.e. 8 ml · kg BM-1) 30 min before and 2 ml · kg BM-1 at 15-min intervals throughout the 1-h run. There were no differences in total distance covered (placebo: 13,680 m, s = 1525; carbohydrate: 13,589 m, s = 1635) (P > 0.05). Blood glucose and lactate concentration, respiratory exchange ratio, and carbohydrate oxidation during exercise were not different between trials (P > 0.05). There were also no differences in ratings of perceived exertion, felt arousal or pleasure-displeasure between trials (P > 0.05). In conclusion, the ingestion of a 6.4% carbohydrate-electrolyte solution did not improve 1-h running performance when a high carbohydrate meal was consumed 3 h before exercise.